Developing a Computer-Controlled Treat Dispenser for Canine Operant Conditioning. Issue 1 (28th October 2020) - Arce, Walker; Stevens, Jeffrey R.
When performing canine operant conditioning studies, the delivery of the reward can be a limiting factor of the study. While there are a few commercially available options for automatically delivering rewards, they generally require manual input, such as using a remote control, in accordance with the experiment script. This means that human reaction times and transmission distances can cause interruptions to the flow of the experiment. The potential for development of non-supervised conditioning studies is limited by this same factor. To remedy this, we retrofitted an off-the-shelf treat dispenser with new electronics that allow it to be remotely controllable as well as act as an experiment computation, data storage, and networking center. We present a fully integrated dispenser driver board with a complementary Raspberry Pi. With rather simple modifications, the commercial treat dispenser can be modified into a computer-controlled dispenser for canine cognition experiments or for other forms of canine training or games.